Nonlinear Model Predictive Control For Bioethanol Fermentation Process - Mohd, Noraini (2014)
The bioethanol fermentation process has a complex dynamics and is inherently nonlinear. The nonlinearity behavior of the process is caused by the variation in the biomass composition with the operating conditions while the constraints inherited by the process increase the process complexity. Due to these reasons, the modelling and the control of the bioethanol fermentation process is difficult and the application of model based control strategies often lead to a better performance. In this work, a Nonlinear Model Predictive Controller (NMPC), which is one of the well-known model control strategies, has been developed to control the product concentration and the fermenter temperature of the bioethanol fermentation process.